Caregivers' role in using a personal electronic health record: a qualitative study of cancer patients and caregivers in Germany - Weis, Aline; Pohlmann, Sabrina; Poß-Doering, Regina; Strauß, Beate; Ullrich, Charlotte; Hofmann, Helene; Ose, Dominik; Winkler, Eva C.; Szecsenyi, Joachim; Wensing, Michel (BMC medical informatics and decision making, 2020)
Particularly in the context of severe diseases like cancer, many patients wish to include caregivers in the planning of treatment and care. Many caregivers like to be involved but feel insufficiently enabled. This study aimed at providing insight into patients’ and caregivers’ perspectives on caregivers’ roles in managing the patient portal of an electronic personal health record (PHR).
Gesehen am 19.10.2020